Commerce and exile: Traces of Jewish diasporas in the Datini papers - José María Pérez Fernández; José Ramón Ayaso Martínez; Chiara Marcheschi (The Journal of European Economic History (JEEH), 2023)
This essay proposes a preliminary approach to some documents in Italian and Hebrew at the Datini archive. Illustrative cases of what we might call the archaeology of paper, Arnau del Vilar's two manuscript bills and Abram Desforn's letter had lain ensconced in Prato for more than 600 years, and they re-emerge now as fragmentary memories of the exile and loss of these two Jewish converts from Barcelona. They are primary sources for the individual biographies of these victims of the pogroms that spread throughout the Iberian Peninsula towards the end of the fourteenth century, and they document some of the books and objects they managed to take with them into exile. As such they constitute evidence of the forced displacement undergone by different communities in the long history of the Mediterranean. Beyond this, they also illustrate the traces they left behind in commercial archives, as well as their use of trade networks and their administrative-logistic protocols to escape persecution and salvage their property. These papers materialize, in short, the intersection of disciplines like economic history, diaspora studies and semiotics.
Keywords: 330; Jews; Migrants; History; Spain; Juden; Migranten; Geschichte; Spanien